Long‐term efficiency for reducing entanglements of nascent polyethylene by a polystyrene‐modified Ziegler‐Natta catalyst. Issue 11 (19th October 2021) - Cao, Yu; Wu, Yanjie; Tang, Xin; Zhou, Qi; Stapf, Siegfried; Mattea, Carlos; Li, Wei
Abstract: The weakly entangled ultrahigh molecular weight polyethylene (UHMWPE) was synthesized by a Ziegler‐Natta catalyst, where the titanium tetrachloride was anchored on the polystyrene (PS)‐modified silica. The PS chains were successfully incorporated into silica hierarchical pores even with the size less than 10 nm through the in situ free‐radical polymerization of styrene. The self‐diffusion coefficient and crystallization of probing molecules inside the pores were investigated by the pulsed field gradient NMR and thermoporosimetry to address the swollen behavior of incorporated PS blocks. This PS blocks compartmentalized the polyethylene chains, where the less entangled UHMWPE was synthesized with an exceptional activity at 70°C. The ubiquitous PS isolators effectively hindered the formation of chains overlaps during the polymerization, showing a long‐term efficiency to reduce the entanglements of nascent UHMWPE even at 4 h of polymerization The toughness/stiffness/strength balance of weakly entangled UHMWPE was significantly improved. Abstract : Proposed mechanism for the synthesis of weakly entangled ultrahigh molecular weight polyethylene using the polystyrene‐modified catalyst.